THE INFLUENCE OF ORGANIZATIONAL CULTURE, COMPETENCE AND SELF-AWARENESS ON PERFORMANCE OF EMPLOYEES IN DINAS KEBUDAYAAN DAN PARIWISATA PROVINSI JAWA TIMUR - Naisya Nur Karimah; Siti Mujanah (Journal of Applied Management and Business, 2021)
This study aims to determine the effect of organizational culture, competence and self-awareness on the performance of the employees of the Culture and Tourism Office of East Java Province. Respondents in this study amounted to 55 employees through the distribution of questionnaires with sampling techniques using saturated samples. This study uses quantitative methods. The data analysis technique used is multiple linear regression analysis. Data processing in this study using IBM SPSS Statistics 23. The results of this study indicate that organizational culture has a significant effect on employee performance, competence has a significant effect on employee performance, self awareness has no significant effect on employee performance. Organizational culture, competence and self-awareness simultaneously have a significant effect on employee performance with a significance value of 0.000 <0.05. The results of the coefficient of determination show a value of 65.7% which means that all independent variables (organizational culture, competence and self-awareness) affect the Employee Performance variable, while the remaining 34.3% is influenced by other variables not examined in this study. From this explanation, the authors suggest evaluating and developing organizational culture, competence and self-awareness in order to improve employee performance.